A Retrospective, Descriptive Analysis of MRSA Infections in a Low-Endemicity Region, Focusing on Empiric Treatment Adequacy - Haapia, Tiina; Vuopio, Jaana; Oksi, Rasmus; Vahlberg, Tero; Silvola, Jaakko; Kanerva, Mari; MRSA Study Group (Dove Medical Press, 2026)
Background:
Previously, MRSA transmission and infections were mostly recognized as healthcare-associated. Community-associated MRSA (CA-MRSA) cases have become increasingly common, also in low-endemicity countries. Hence, also doctors in outpatient care encounter these patients. Despite increased general awareness on risk factors of MRSA carriage, it does not always influence clinical practice. As the total number of MRSA cases had increased in our region, it provoked us to analyze how this may have reflected the recognition of these infections and their empiric treatment adequacy in Hospital District of Southwest Finland (HDSWF).
Methods:
All new MRSA cases detected between 2007 and 2016 in Hospital District of Southwest Finland were retrospectively analyzed. This single-center study describes MRSA carriers, whose carriage was first detected from a clinical specimen. The cases were recognized from the hospital’s MRSA registry, and their background data, including the antibiotic treatments given, were collected manually from electronic patient records.
Results:
A total of 280 MRSA cases having an active clinical infection were detected. Skin and soft tissue infections (SSTIs) were the most common infection type (76%; 213/280 cases). Information on antibiotic treatments were obtained in 46.8% (131/280) of the cases. In 81.7% (107/131) of the cases, the empiric treatment did not cover MRSA. After adjusting the treatment according to susceptibility results, MRSA was ultimately covered in 49.3% (68/138) of the cases.
Conclusion:
In low-endemicity settings, skin infections typically caused by S. aureus may be missed to being caused by a resistant pathogen, resulting in suboptimal or ineffective treatment. More awareness is needed to recognize the risk, to evaluate and possibly adjust the treatment.